A Review of Wearable Antennas for 5G and Body-Centric Wireless Communication - Suhas R. Kale; Dipak P. Patil (Приборы и методы измерений)
Wearable antennas for body-centric wireless communications have become very popular recently. Wearable antennas are body worn as a part of clothing on the human body and enable hands-free operation, which should also be comfortable. The latest 5G wireless technology has many advantages over 4G like high data transmission rate, low latency, etc. With the help of advanced and innovative technologies, wearable antennas can be developed using various materials. This paper presents a detailed review of the application of wearable antennas designed specifically for 5G and body-centric wireless communications. It also presents the selection of materials for the antennas and different fabrication techniques. The paper also looks at the bending of antennas at different radii and analyzes its impact on durability.